Security in Computing and Communications : 6th International Symposium, SSCC 2018, Bangalore, India, September 19–22, 2018, Revised Selected Papers /: 6th International Symposium, SSCC 2018, Bangalore, India, September 19–22, 2018, Revised Selected Papers. (2019) - Unknown
No abstract available